2012
DOI: 10.1353/jda.2012.0019
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality, Economic Development, and Globalization: A State Level Analysis of India

Abstract: This study using access to education and health as the indicators of gender inequality examines gender inequality and state level openness in the different states of India. Further, the study"s findings show that at the sub-national level in India higher per capita income is accompanied with lower gender inequality. However, in some high income states gender inequality is also very high. High gender inequality was also observed in the states which score high in the openness index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 28 publications
3
27
1
6
Order By: Relevance
“…Another factor that could warrant for this outcome could be the ghost worker 15 syndrome which has plagued the Nigerian public sector for decades [54], [55], [56] and [57]. This is an act of stealing from the State and Federal Government at large under the disguise of paying wages to employees that do not exist in person without due contribution to the productivity of the Nigeria civil service and public sector as a whole.…”
Section: A Female Labour Employment In the Civil Service And Economimentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that could warrant for this outcome could be the ghost worker 15 syndrome which has plagued the Nigerian public sector for decades [54], [55], [56] and [57]. This is an act of stealing from the State and Federal Government at large under the disguise of paying wages to employees that do not exist in person without due contribution to the productivity of the Nigeria civil service and public sector as a whole.…”
Section: A Female Labour Employment In the Civil Service And Economimentioning
confidence: 99%
“…[36] and [58], posited that ensuring the participation of women in paid employment would benefit the economy via women's contribution to saving, and spending behaviour. As advanced by [59], women participation in paid employment affords women an independent income stream that convalescent women's 15 Ghost workers refers to fictitious and non-existing employees that are on payroll [54]. intrahousehold bargaining power and, improves their socio-economic status by allowing them to accumulate human capital.…”
Section: A Female Labour Employment In the Civil Service And Economimentioning
confidence: 99%
“…Com isso, o salário relativo e a empregabilidade cresceram entre as mulheres que compunham a força de trabalho operária, mas não afetou significativamente as que trabalhavam em cargos administrativos. Arora (2012) verifica quais os impactos da globalização e do desenvolvimento econômico na desigualdade de gênero para os diferentes estados da Índia. O autor mostra que, ao mesmo tempo em que estados com elevada renda per capita possuem baixa desigualdade de gênero, existem também alguns estados em que uma alta renda per capita coincide com alta desigualdade, de modo que renda elevada não parece ser determinante para equidade de gênero.…”
Section: Revisão Da Literaturaunclassified
“…O índice de igualdade de gênero (IIG) contempla quatro fatores distintos, conforme discutido na seção anterior. Com o objetivo de entender fatores que explicariam a melhoria do IIG dentro dos estados brasileiros, neste artigo recorre-se à literatura anterior focada em diferenças na equidade de gênero ocasionadas por alterações em medidas de desenvolvimento econômico (Lagerlöf, 2003;Dollar and Gatti, 1999;Gumbel, 2004), globalização (Arora, 2012;La Ferrara, Chong e Duryea, 2012;Oostendorp, 2004;Baliamoune-Lutz, 2006; Juhn, Ujhelyi e Villegas-Sanchez, 2013; Mukhopadyay and Chaudhuri, 2013) e bem-estar (Schneider, 2013;Bárcena-Martín e Moro-Egido, 2013;Seguino, 2006).…”
Section: Modelagem Empírico-teóricaunclassified
“…A large number of studies based on cross-country results have also highlighted the role of gender in economic growth and development. At an aggregate level, these studies have shown that inequality in gender is bad for economic growth and lower the gender inequality, higher is per capita income and economic growth (Arora, 2012). Today, in the era of globalization where the world is vocal about providing equal opportunities to the fairer sex, the data from developed and developing countries show a different picture altogether.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%